An approach to the Integrated Design and Development of Manufacturing Systems - Nylund, H.; Salminen, K.; Andersson, P. H. (Cranfield University Press, 2009)
This paper describes an approach to integrated manufacturing systems. It aims to integrate design and development activities, as well as the entities existing in a manufacturing system. A model of manufacturing systems is presented, including manufacturing entities with different roles and domains related to them. The characteristics of the manufacturing entities are discussed, including changeability, service orientation, and learning capabilities. One of the main enablers is a digital manufacturing system, which includes tools for modeling, simulation and analysis, as well as digital information and knowledge. This is illustrated by an example process, from product ideas to the efficient production of the products.
Organised by: Cranfield University
Keywords: Manufacturing System; Integration; Design; Development